Differential responses of littoral communities to ultraviolet radiation in an alpine lake - Leavitt, P. R.; Vinebrooke, R. D. (1999)
Differential sensitivities of benthic and planktonic communities to UV radiation may involve differences in habitat conditions (e.g., availability of physical refuge), taxonomic composition, UV-A (320-400 nm) and DNA-damaging UV-B (280-320 nm) irradiances, and potential indirect effects via food-web processes. These hypotheses were tested using 18 enclosures (corrals) within an alpine lake. The factorial design consisted of three UV treatments (+ UV, - UV-B, - UV) and two macroinvertebrate densities (ambient, 3x), High performance liquid chromatography was used to quantify changes in periphyton and phytoplankton abundance and composition in response to UV radiation and macroinvertebrates over a period of 1 mo. Algal and invertebrate responses to UV radiation were habitat- and taxon-specific. Epilithic standing crop was significantly suppressed by UV radiation, primarily due to UVB radiation inhibiting diatoms by 40%. In contrast, standing crop of epipelic (sediment-dwelling) organisms was significantly enhanced by UV-A radiation, which increased the abundance of cyanobacteria by 50%. UV radiation also significantly altered the taxonomic composition of both epilithon and epipelon. In comparison, picocyanobacterial phytoplankton were unaffected by UV radiation. Zoobenthos (Gammarus lacustris, Chironomidae) and zooplankton (Hesperodiaptomus arcticus, Rotifera) did not significantly alter periphyton or phytoplankton biomass or taxonomic composition. Although total zoobenthos and zooplankton biomass were unaffected by UV radiation, UV-B significantly suppressed the final density of rotifers but not that of heavily pigmented calanoid copepods. These results show that UV radiation affects shallow-water communities in cold and unproductive systems mainly through direct effects, rather than by indirect effects mediated by food-web processes. Access to physical refuges was evidently a key factor determining habitat-specific responses to UV radiation. UV radiation did not adversely affect motile epipelon and zoobenthos ...